Inspiration of Women's Leadership in the Qur'an - Muhammad Amin; Nawawi Marhaban; Maula Sari (At-Tafkir, 2022)
Women have always been an interesting topic to discuss, and the discussion of women gets a sizable portion in the Qur'an. But unfortunately, there are still some narrow views in patriarchal culture that discriminate against women. This paper aims to highlight and analyze in depth the virtues and privileges of women in the Qur'an, which so far are still considered as subordinates. The method used in this study is a library research method with a semantic approach, this approach is used to examine the verses of the Qur'an related to the privileges of women and who the women mentioned in the Qur'an are. The results showed several women mentioned in the Qur'an Maryam, Fatât Madyan, Imara'atu Fir'ûn, Malika Saba', Imra'atu Imran, Maryam bint Imran and Khaulah bint Tha'labah. Their stories in the Koran confirm that women have excelled in both spiritual and professional careers, and that their strengths aren't domination by one gender. This argument gives a different perspective that women also have equal opportunities to achieve, do good, and enter the political, leadership, social and economic spheres.